Grief and deceased-related digital culture: An exploratory, longitudinal, qualitative inquiry - O'Connor, Mórna N. (2021)
This thesis is about the diverse digital material produced in the course of contemporary lives, and the role of this material for those who mourn these lives. To study this, I applied three fundamental principles of grief theory and research to this novel empirical terrain. The result is an exploratory, longitudinal, qualitative exploration of grief and deceased-related digital material in the experiences of thirty-two survivors, constellated around eleven cases of digital-age death.